Process And Post-Processing Optimization Of A High-Strength Aluminum Matrix Composite Fabricated By LPBF - Bona, M.; Agostoni, G.; Fantoni, G.; Tirelli, M.; Mattia, G.A. (My University, 2025)
Laser Powder Bed Fusion (LPBF) enables the production of complex aluminium components, but high-strength alloys like 2024 are prone to hot cracking. This work investigates the processability of a modified Al-Cu-Mg alloy containing titanium and ceramic grain refiners, which enhance printability and reduce defect formation. Laser power and scanning speed were varied under two different layer thickness configurations to assess their influence on density and mechanical performance. In both cases, relative densities above 99.5% were achieved. However, the low layer thickness condition led to superior mechanical properties, with a peak microhardness of 163.7 HV, compared to 154 HV for the high layer thickness. Post-processing heat treatments were applied to selected samples, including direct ageing and two solution plus artificial ageing routes. These thermal cycles enabled the development of different microstructures and resulted in improved mechanical performance in selected cases.